Las comunidades arvenses estivales de los barbechos y rastrojos alzados de los sectores Somontano-Aragonés y Bárdenas-Monegros: Kickxio lanigerae-Chrozophoretum tinctoriae Izco 1975 - Sanz Elorza, Mario (Lazaroa, 2001)
After studying the summer weed communities growing in the ploughed stubbles and frequently farmed fallows of the Somontano-Aragonés and Bárdenas-Monegros chorological sectors (Aragón province), we believe sufficient floristic differences exist to recognise a new subassociation: Kickxio lanigerae-Chrozophoretum tinctoriae Izco 1975 amranthetosum blitoidis. It is clearly characterised by the constant presence of the species Amaranthus blitoides, the absence of Kickxia lanigera and its overall impoverishment compared with is counterparts in Castile and La Mancha.